SIMULASI PROSES PEMBAKARAN PADA MOTOR BAKAR TORAK DUA LANGKAH - Soelaiman, T. A Fauzi; Bachrun, Rachmat K; Mangaranap, Arthur M; Arifin, Andry (Mesin, 1998)
The combustion process in an intemal combustion engine must be known in detail to ï¬nd out the dependence of its operating conditions on the engines performance. This paper discusses a computer program that simulates the combustion processes of a two-stroke engine. The simulation includes modelling the heat transfers from the cylinder and crankcase, modelling the heat releases for gasoline and diesel engines, modelling the gas properties, modelling the energy balance, and modelling the ï¬ow coefficients through the ports. The performance of the two-stroke engine can be obtained from the simulation. As a case study, a two stroke MK1 engine was simulated and the simulation results the maximum indicated power is 18.3 hp at 5500 rpm and the maximum indicated mean effective pressure (IMEP) is 4.2 bar at 5000 rpm.